(untitled) (Anwer Khan Modern Medical College Journal, 2012)
The word ’eponym’ is derived from the Greek ’epi’ which roughly means ’upon’ and ’onyma’ which means ’name’. Strictly speaking, an eponym is a word derived from the name of an actual person or a fictional or mythical character1. Eponyms have been officially excluded from anatomical nomenclature. Yet whether we like them or not, criticize them as archaic and unscientific, anatomical eponyms are still in current use, especially amongst clinicians2. The following paragraphs will cover the life events few famous eponymous anatomists who are renowned for their contribution to the field of anatomy. DOI: http://dx.doi.org/10.3329/akmmcj.v3i1.10109 AKMMCJ 2012; 3(1): 20-23